2022
DOI: 10.3390/pharmaceutics14010098
|View full text |Cite
|
Sign up to set email alerts
|

SonoVue® vs. Sonazoid™ vs. Optison™: Which Bubble Is Best for Low-Intensity Sonoporation of Pancreatic Ductal Adenocarcinoma?

Abstract: The use of ultrasound and microbubbles to enhance therapeutic efficacy (sonoporation) has shown great promise in cancer therapy from in vitro to ongoing clinical studies. The fastest bench-to-bedside translation involves the use of ultrasound contrast agents (microbubbles) and clinical diagnostic scanners. Despite substantial research in this field, it is currently not known which of these microbubbles result in the greatest enhancement of therapy within the applied conditions. Three microbubble formulations—S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Surprisingly, the increase in MB concentration did not affect the permeabilization efficiency of spheroids (Figure A,B). The data available in the literature showed that the permeabilization of cells and tissues is dependent on the MB concentration. In the near future, the influence of a wider range of MB concentrations as well as the type of MBs ( i.e. , soft- vs hard-shelled MBs, bare vs targeted MBs, poly- vs monodisperse MBs, etc. )…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the increase in MB concentration did not affect the permeabilization efficiency of spheroids (Figure A,B). The data available in the literature showed that the permeabilization of cells and tissues is dependent on the MB concentration. In the near future, the influence of a wider range of MB concentrations as well as the type of MBs ( i.e. , soft- vs hard-shelled MBs, bare vs targeted MBs, poly- vs monodisperse MBs, etc. )…”
Section: Discussionmentioning
confidence: 99%
“…Sonovue was the most widely used UCA in previous studies, but its mechanical properties limit its use with high-frequency linear array probes for breast scanning and its capacity for long-term imaging. In our study, Sonovue imaging could only last 4 minutes, limiting access to high-quality imaging parameters compared to the more stable Optison or Sonazoid (28). External perfusion software, such as VueBox (Bracco, Italy), with integrated motion correction, allows for a more detailed evaluation of micro vascularization in terms of wash-in and wash-out kinetics because cine loops for up to 2min can be evaluated and more parameters are determined (29).…”
Section: Discussionmentioning
confidence: 99%
“…Study population characteristics included number of patients, age, gender, number of liver transplantation, type of transplant, and follow up duration. Abstracted data included contrast agents (SonoVue‐sulfur hexafluoride lipid shells, Levovist‐lipid/galactose shell, and Optison‐octafluoropropane protein shells), 17, 18 indication for CEUS, diagnostic criteria for CEUS, reference standard, prevalence of HAO, prevalence of HAS, prevalence of HAT, sensitivity, specificity, true positive, false positive, false negative, and true negative. This information was either obtained directly from the study or calculated using other information.…”
Section: Methodsmentioning
confidence: 99%